The Ethics of Seeking and Conveying Knowledge: A Study of Ibn Majah's Hadith No. 220 Based on Hadith Science and Scientific Practice - Iswandi, Iswandi; Sudrajat, Hendra; Meor Muhammad Afif Aiman Abu Bakar; Slamet Riyadi (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2025)
Islamic education faces the challenge of integrating Islamic values ​​into a modern context, particularly regarding the obligation to seek knowledge and the ethics of imparting it. This study aims to analyze the Hadith of Ibn Majah No. 220 in the context of education, focusing on the implications of this teaching for contemporary educational practices. The method used is a qualitative approach, through analysis of the Hadith text and interviews with educators. The results show that this Hadith emphasizes the importance of the obligation to seek knowledge as a foundation for education, while also highlighting the role of ethics in imparting knowledge. These findings have significant implications for the development of values-based educational curricula and ethics training for educators, and encourage further research to examine the application of this teaching in broader contexts. Thus, this study contributes to the development of a more responsive and ethical Islamic education.